2012
DOI: 10.1161/circulationaha.111.089409
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Extracellular Matrix Expansion Quantified by Cardiovascular Magnetic Resonance and Short-Term Mortality

Abstract: Background Extracellular matrix (ECM) expansion may be a fundamental feature of adverse myocardial remodeling, appears to be treatable, and its measurement may improve risk stratification. Yet, the relationship between mortality and ECM is not clear due to difficulties with its measurement. To assess its relationship with outcomes, we used novel, validated cardiovascular magnetic resonance (CMR) techniques to quantify the full spectrum of ECM expansion not readily detectable by conventional CMR. Methods and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
327
3
6

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 438 publications
(349 citation statements)
references
References 42 publications
(76 reference statements)
6
327
3
6
Order By: Relevance
“…Even a connection between elevated ECV and mortality prediction was reported. In a study with 793 patients suffering from ischemic heart disease, ECV showed potential in the prediction of short-term mortality [15]. T2 mapping, however, enables the identification of myocardial edema in acute infarction and inflammatory disease [16].…”
Section: Introductionmentioning
confidence: 99%
“…Even a connection between elevated ECV and mortality prediction was reported. In a study with 793 patients suffering from ischemic heart disease, ECV showed potential in the prediction of short-term mortality [15]. T2 mapping, however, enables the identification of myocardial edema in acute infarction and inflammatory disease [16].…”
Section: Introductionmentioning
confidence: 99%
“…14 An association between ECV, short-term death, and other adverse clinical outcomes also has been recently shown 9 ; this association appears to be stronger with ECV than with LGE. 7 On the basis of this association, the use of ECV as a biomarker for risk stratification has been proposed.…”
Section: T1 Mapping and Extracellular Volume Quantificationmentioning
confidence: 89%
“…Consequently, it can be said that ECV attempts to divide the myocardium into its cellular and interstitial components, with estimates expressed as volume fractions. 7 Extracellular volume maps are generated by quantifying the native and postcontrast T1 values on co-registered images while adjusting for the hematocrit, 9 in order to account for the effects of changes in body composition, renal function, and hematocrit due to the underlying disease process.…”
Section: T1 Mapping and Extracellular Volume Quantificationmentioning
confidence: 99%
See 1 more Smart Citation
“…47 Alterations in these compartments occurring from different physiologic and pathophysiologic biologic processes leading to fibrotic changes can be more easily detected with ECV than with LGE. 51 This is true especially with the changes resulting from pathologies other than MI, where the differences between the normal and affected myocardium are less distinct. 47,[51][52][53] Therefore, the more widespread clinical use of these tissue characterization techniques requires further exploration.…”
Section: Myocardial T1 Mapping and Extracellular Volume (Ecv) Fractionmentioning
confidence: 99%